The need for improved maps of global cropland - Fritz, Steffen; See, Linda; You, Liangzhi; Justice, Chris; Becker-Reshef, Inbal; Bydekerke, Lieven; Cumani, Renato; Defourny, Pierre; Foley, Jon; Gilliams, Sven; Gong, Peng; Hansen, Matthew; et al. (Wiley, 2013)
Food security is a key global concern. By 2050, the global population will exceed 9 billion, and a 50% increase in annual agricultural output will be required to keep up with demand. There are significant additional pressures on existing agricultural land through increased competition from the biofuel sector and the need to elevate feed production, which is being driven by higher levels of meat consumption in low- and middle-income countries.